(untitled) (The Review of Diabetic Studies, 2025)
Background Saudi Arabia being a major pilgrimage center with an annual turnover of millions of pilgrims from all over the world has a high risk for transmission of infections; Health care workers (HCWs) are particularly vulnerable to these infections. The objectives of this research were to assess impact of the infection control standard among health care workers during the Hajj in Saudi Arabia, the role of pre deployment Hajj training of HCWs assigned Hajj duties with those HCWs. The mass gathering of pilgrims during the Hajj season from different countries with various epidemiological backgrounds creates a situation, which increases the risk of spread of infection both to the visiting pilgrims and their contacts on return home and health care workers. Healthcare infection control standard among health care workers during Hajj infections have been a critical cause of morbidity and an undue burden in the healthcare system in Saudi Arabia. Protocols of infection control standard management during the Hajj urge the significance of these measures to infection prevent the spread of contaminated organic essential fluids, the administration of harmful gases, and the proper disposal of hazardous bio-waste products. Unsafe practices in dealing with needle sticks, sharp instruments, contamination of the wound surface, Aim of study: To determine the Impact of the infection control standard among healthcare workers (HCWs) during the Hajj in Saudi Arabia 2025. Methods: Through cross sectional study design a randomly selected sample of health care workers during Hajj duties in 2025 were part of Hajj. Participants were taken from different Makkah region primary health care . A validated self-administered questionnaire was used to Impact of the infection control standard of (300) health care workers. Results: most of the participants (30.0%) were in the age group(30-49) years follow by the age 50-60 were (27.0%) followed by 30-39 years were (23.0) Conclusion: Our research highlighted the gaps in knowledge of the health care workers during the Hajj practicing the knowledge and practice. However previse study’s concludes that even though the infection control standard among health care workers during the Hajj but there was a lack of practice. As infection control routine trainings are limited, gaps have been identified in knowledge and practice of infection control during the Hajj.